Strategi Pengembangan Agrowisata Di Green Camp - Agustinus Antonius Mau Loko; Ketut Arnawa; Ni Gst. Ag. Gde Eka Martiningsih (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2020)
Agro-tourism is part of a tourist attraction that utilizes agricultural business (agro) as a tourist attraction. The aim is to expand knowledge, recreational experience, and business relationships in agriculture. Through the development of agrotourism that emphasizes local culture in utilizing land, we can increase farmers' incomes and conserve land resources, as well as maintain local culture and technology (indigenous knowledge) which are generally in accordance with the conditions of their natural environment. Research Objectives Identify internal and external factors that are strengths, weaknesses, opportunities and threats for the development of Green Camp agrotourism. Formulate the right strategy to achieve maximum results in the development of Green Camp agro-tourism. The number of samples in this study were 6 respondents, the method of determining the sample by population or census methods. The analysis technique uses SWOT analysis. The results showed the identification of internal strategic factors in Green Camp Agro Tourism that became strengths was maintaining complete facilities such as parking lots, toilets, education rooms and organic gardens, the only unique, skilled management, while internal factors that became weaknesses were tourists not coming every day, promotion is still lacking, the road to the location is still damaged, foreign language skills are still lacking. Identification of external strategic factors in the Green Camp Agro Tourism becomes an opportunity is visitors are dominated by foreigners, close to other tours, young access to Green Camp Agro Tourism, government support and private sector. While the strategic factor that poses a threat is that tourist visits are difficult to predict, limited parking space still occurs during holidays. Strategy in the development of Green Camp Agro Tourism using the SWOT Matrix. Strategies using strengths that take advantage of opportunities are (SO), which is to maintain tradition by always presenting traditional snacks at the Green Camp Agro Tourism, then (ST) always holding interesting performances so that there are differences with other tourism, (WO) conducting training and workshops to the management in improving employee's foreign language skills and (WT) training on marketing to administrators.